The Effect Of Marketing Mix, Quality Of Service And Orientation Of Entrepreneurship To Competitive Advantages The People's Market In Surabaya City - Beni Agus Setiono (Journal of Indonesian Science Economic Research, 2019)
This study aims to prove and analyze the effect of marketing mix, service quality and entrepreneurial orientation on the competitive advantage of people's markets in the city of Surabaya. The method used in this research is a survey conducted on a market unit under the auspices of the Pasar Surya Regional Company in Surabaya. The population in this study were all public market units managed by the Pasar Surya Regional Company in Surabaya City and those that were still active were 67 public market units. The number of samples 135 respondents with an observation unit of 675 traders or tenants of the Surabaya municipal market area Surabaya city. The data used in this study are primary data sourced from questionnaires. data analysis and hypothesis testing in this study using Multiple Linear Regression. The results showed that the marketing mix, service quality and entrepreneurial orientation had a significant positive effect on the competitive advantage of the people's market in the city of Surabaya.